Long‐term single‐center comparison of ICD lead survival: Evidence for premature Linox lead failure. (27th April 2018) - O'Connor, Matthew; Hooks, Darren; Webber, Matthew; Shi, Bijia; Morrison, Stephanie; Harding, Scott; Larsen, Peter
Abstract: Introduction: ICD lead failure is a potential source of significant morbidity and mortality. This study investigates the survival rates of Sprint Quattro, Endotak Reliance, and Linox ICD leads. Methods and results: A retrospective cohort study of all patients with an ICD implanted between January 2007 and December 2012 from the Wellington Hospital region, New Zealand, a tertiary referral center. Lead and patient details were established by review of clinical notes and the PaceArt Optima database. We analyzed a total of 287 implants using Sprint Quattro (n  =  92), Endotak Reliance (n  =  37), Linox (n  =  151), Riata (n  =  4), and Sprint Fidelis (n  =  2) leads. Median follow‐up was 61.6 (26.0–81.6) months for Sprint Quattro leads, 66.7 (53.3–88.8) months for Linox leads, and 82.9 (45.9–107.4) months for Endotak Reliance leads. There were 20 cases of lead failure of which 19 were in Linox leads. The 4‐, 6‐, and 8‐year survival for Linox leads was 97% (92.6–99.1), 93% (85.5–96.5), and 76% (62.3–85.5), respectively. The predominant abnormality was detection of nonphysiological electrical signals. Linox lead failure was associated with a younger age of patient (49.2 vs. 57.7 years, P  =  0.007). Conclusions: The 7‐year survival of Linox leads was significantly worse than shown in Biotronik surveillance reports, but in line with other single‐center studies from around the world.